THE MEDIATING ROLE OF SELF-LEADERSHIP STRATEGIES IN THE EFFECT OF JOB AUTONOMY ON INNOVATIVE WORK BEHAVIOR AMONG 2024 PROBATIONARY LECTURER AT HALU OLEO UNIVERSITY - Ningtyas, Ajeng Purwati; Hamris, Saddiya; Wulan Ramadhanty, Pramesty; Shalahuddin (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
The purpose of this study is to investigate how job autonomy affects creative work practices among 2024 probationary lecturer at Halu Oleo University, using self-leadership techniques as a mediating variable. A closed-ended questionnaire with a 5-point Likert scale was used to gather data using a quantitative causal-associative technique. The questionnaire was disseminated online using Google Forms. Using a census method, a final sample of 75 respondents was selected from the population, which included 93 lecturers. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data. with SmartPLS software. The results show that job autonomy has a positive and significant effect on innovative work behavior and self-leadership strategies. Furthermore, self-leadership strategies have a positive and significant effect on innovative work behavior and mediate the relationship between job autonomy and innovative work behavior. These findings highlight that granting adequate job autonomy, combined with the development of self-leadership skills, plays a crucial role in fostering innovative work behavior among lecturers.